Estimation of the Impact Duration for Several Types of Structures - E. Jacquelin; S. Pashah; J.P. Lainé; M. Massenzio (Shock and Vibration)
The impact duration between two structures is not easy to forecast. Indeed it depends on many parameters including local parameters as well as structural parameters which characterize the dynamics of the structures.